The Implementation of the Potensia Apps for Online Psychological Assessment during the Pandemic for Highschool Students in West Sumatra - Ardi, Zadrian; Jasril, Ilmiyati Rahmy; Yendi, Frischa Meivilona; Guspriadi, Yan (Jurnal Aplikasi IPTEK Indonesia, 2022)
Psychological assessment is an essential aspect of the implementation of counseling services. However, efforts to study needs by school counselors have yet to be optimal. The impact is the preparation of counseling service programs, and the level of accuracy in disclosing the psychological conditions of students and clients decreases. The process of downstream and disseminating the results of this research was carried out through community service activities to increase the distribution and utilization of research results for guidance and counseling teachers in Indonesia. This activity was carried out within two years. The method used is advanced training for school counselors in all districts/cities in West Sumatra with a focus on several schools appointed by partners, upgrading applications based on FGDs, improving application management, and commercializing the POTENSIA Android application. So far, the achievements and progress of program implementation have been the implementation of activities by presenting more than 60 school counselors from all over West Sumatra using the workshop method.